Food service equipment - Hightower, Monica; Creative Educational Video Inc. (Cubbock, Texas : Creative Educational Video, 1995)
Covers the use and handling of knives, kitchen tools, and measuring devices
Camera, Monica Hightower, Ricky Martines, Jay Alan Hoes ; executive producer, G.W. Davis
Narrator : Jay Alan Hoes
Senior high school and vocational students
Keywords: Food service -- Equipment and supplies; Industrial hygiene